The impact of domestic and foreign direct investments on economic growth: evidence from ASEAN countries - Almasaied, Suleiman W.; Baharumshah, Ahmad Zubaidi; Rashid, Salim (Universiti Putra Malaysia Press, 2008)
In this paper, the dynamic relationships between foreign direct investment (FDI), domestic investment and other determinants of economic growth were examined. Both the short-run and long-run growth processes were modelled using the ARDL approach to carry out cointegration analysis for five ASEAN countries. The main results included (i) domestic investment, FDI, human capital and financial intermediation significantly affected economic growth; (ii) FDI had a positive and significant effect on growth but this was of lesser magnitude as compared to domestic investment; and (iii) a strong support was found for an export-led-growth hypothesis, and the impact of technology transfer from international trade was larger than direct technology transfer from FDI. All in all, our empirical results from the ASEAN countries confirm the view that investments and exports are the engines of growth and it is worthwhile for the authorities to encourage domestic as well as foreign capital to put these countries back on their pre-crisis growth paths.